Taxonomic notes and Corrigendum for the manuscript entitled “Ichneumonid wasps of the subfamily Mesochorinae (Hymenoptera: Ichneumonidae): new replacement names, combinations and an updated key to the World genera” ARAUJO et al. (2018), Zootaxa, 4521: 052–060. - Araujo, Rodrigo O. (Zootaxa, 2018)
Mesochorinae is a widely distributed subfamily of ichneumonid wasps with approximately 900 described species (Yu et al., 2012), of which almost 90% belong to the cosmopolitan genus Mesochorus Gravenhorst (Broad et al., 2018). Since it is a very large genus, it has become a group of complex taxonomy and with numerous taxonomic conflicts (Araujo et al., 2018). Recent efforts were made aiming to resolve nomenclature problems present within Mesochorus (see Araujo & Vivallo, 2015; Kittel, 2016; Araujo et al. 2018). Specifically, Araujo & Vivallo (2015) and Araujo et al. (2018) proposed a total of 19 replacement names, of which two became primary homonyms of existing names (listed below) and seven were invalid, as Kittel (2016) and, in one case, Schwenke (2002), had previously proposed respective replacement names. Furthermore, Araujo et al. (2018) published an identification key for the World genera of Mesochorinae which includes Incurvarion Kasparyan. However, this genus was implicitly synonymized with Neurogenia Roman (Ctenopelmatinae: Perilissini) when Reshchikov et al. (2014) transferred the type (and only included) species, I. gorochovi Kasparyan, to Neurogenia. To resolve the taxonomic conflicts that remain within the subfamily Mesochorinae, seven new synonymies and two replacement names are proposed herein, together with a corrigendum for the identification key proposed by Araujo et al. (2018).